THE PECULIARITIES OF TRANSLATION OF PROVERBS FROM ENGLISH INTO UZBEK - Bozorova , Maftuna Xamza qizi (Educational Research in Universal Sciences, 2023)
This article explores the intricacies involved in translating English proverbs into Uzbek, shedding light on the challenges posed by linguistic and cultural differences. The study employs a comparative analysis of selected proverbs, examining lexical and syntactic structures, cultural nuances, and communicative effectiveness. The results offer valuable insights into the complexities of cross-cultural communication through proverbial expressions, emphasizing the importance of context-aware translation.